(untitled) - Food and Agriculture Organization of the United Nations (Rome, Italy, 2008)
The second Working Party on Fisheries Data and Statistics was attended by participants from Comoros, France, Kenya, Madagascar, Mauritius, Mozambique, Seychelles, Somalia, South Africa, the United Republic of Tanzania, Yemen, the Indian Ocean Tuna Commission (IOTC), the Regional Programme for the Sustainable Management of the Coastal Zones of the Indian Ocean (ReCoMap) and the South West Indian Ocean Fisheries Project (SWIOFP). The Working Party received updates of the status of monitoring of the fishery catches by the member countries of the South West Indian Ocean Fisheries Commission. Some countries were upgrading their systems, others continued with existing systems that operated satisfactorily. Comoros and Somalia had no systems in place. The Working Party discussed minimum data requirements for effective fisheries management in three artisanal fishery types: tuna, shark and small pelagic fisheries. Each country provided the existing availability of data for these requirements. As requested, the Working Party also examined the standardization and synchronization of frame surveys from a technical presentation on frame survey design as well as from information provided by the countries at the meeting. Due to the large variety of artisanal vessels in the region a more detailed analyses would be required in order to provide recommendations to the Scientific Committee.
Keywords: Fisheries management,Fisheries,Quản lý nghề cá,Nghề cá; Statistics,Số liệu thống kê